Effect of live weight pre- and post-lambing on milk production of East Friesian sheep - Angeles Hernandez, Juan C.; Radic Schilling, Sergio Javier; Vera Arias, Marcela A.; Echeverria Perez, Ricardo Andres; Alonso Castelan-Ortega, Octavio; Ramirez Perez, Aurora H.; Gonzalez Ronquillo, Manuel (My University, 2018)
The study was conducted to analyse the effect of sheep body weight (BW) at mating, mid-pregnancy, lambing, early lactation, mid-lactation and late lactation on milk yield and patterns of milk production. Also, the effects of environmental factors such as number of lambing (NL) and type of lambing (TL) on BW and milk production were analysed. A total of 52 multiparous East Friesian ewes from an experimental flock were used. Ewes were assigned to three different groups according to their BW at each productive stage: low (LBW), moderate (MBW) and high BW (HBW). Lactations were fitted using the mechanistic model described by Pollott. Total milk yield (TMY), peak yield (PY) and time at peak yield (TPY) were also calculated. HBW ewes had consistently higher TMY (p < .001) and PY (p < .05) values, than LBW and MBW in most of productive stage measured. There was a positive linear relationship (p < .05) between TMY and BW in all-productive stage, except at mid-gestation where the relationship was quadratic. HBW ewes weighted at mid-pregnancy showed the highest values of maximum secretion parameter (p = .04) of Pollott model, which could partially explain the better milk yield of HBW ewes. A significant effect of NL on BW (p = .007) and TMY (p = .007) was observed. The BW ewe's in pregnancy and early lactation is a useful indicator at farm level to improve the milk yield performance in dairy sheep.
Keywords: milk yield; dairy ewe; pregnancy; live body weight